PENGARUH PENYINGKAPAN KEBERLANJUTAN TERHADAP PENGEMBALIAN SAHAM PADA BANK UMUM DI INDONESIA - Azman Ghalib Ibrahim; Atika Irawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Every company shared one same goal which is to maximize the shareholder’s wealth. In order to do that, companies have several options such as increasing their profit, increase the company’s value, and do sustainability initiative. The sustainability option has gained more attention from the public recently. However, studies show different results about the effect of the sustainability initiative in increasing the shareholder’s wealth in different industries. In determining the shareholder’s wealth, several studies use different proxy such as stock price, stock return, and company performance. While in this research, stock returns will be used because it shows how the stock price perform in a period of time. This research aimed to determine the effect of the sustainability in the banking industry because bank is considered as one of the most important industries in a country. To analyze it, a panel data regression was done using STATA 17.0 with 13 commercial banks in Indonesia from 2017-2022 as the sample. The results shows that only the social aspect that has a positive effect on the stock return of banks and for the economic and environmental aspects does not have any effect on the stock return of banks. This indicates that banks can maximize their shareholders’ wealth by paying more attention on the social aspect of sustainability.